FlyBase: updates to the Drosophila melanogaster knowledge base. Issue Volume 49:Issue D1(2021) (21st November 2020) - Larkin, Aoife; Marygold, Steven J; Antonazzo, Giulia; Attrill, Helen; dos Santos, Gilberto; Garapati, Phani V; Goodman, Joshua L; Gramates, L Sian; Millburn, Gillian; Strelets, Victor B; Tabone, Christopher J; Thurmond, Jim; et al.
Abstract: FlyBase (flybase.org) is an essential online database for researchers using Drosophila melanogaster as a model organism, facilitating access to a diverse array of information that includes genetic, molecular, genomic and reagent resources. Here, we describe the introduction of several new features at FlyBase, including Pathway Reports, paralog information, disease models based on orthology, customizable tables within reports and overview displays ('ribbons') of expression and disease data. We also describe a variety of recent important updates, including incorporation of a developmental proteome, upgrades to the GAL4 search tab, additional Experimental Tool Reports, migration to JBrowse for genome browsing and improvements to batch queries/downloads and the Fast-Track Your Paper tool.